HUBUNGAN PEMANFAATAN SOSIAL MEDIA FACEBOOK DENGAN KOMPETENSI PETANI TANAMAN SAYURAN DI DESA LALOSINGI KECAMATAN LALOLAE KABUPATEN KOLAKA TIMUR - Suci Aulia Mustaming; Iskandar Zainuddin Rela; Megafirmawanti Lasinta (Jurnal Ilmiah Inovasi dan Komunikasi Pembangunan Pertanian, 2023)
This study aims, namely to find out how the utilization of Facebook social media, to find out how the competence of farmers in cultivating vegetables, and to determine the relationship between the utilization of Facebook social media with the competence of vegetable crop farmers. The research was conducted on all vegetable farmers who use Facebook social media in cultivating vegetable crops in Lalosingi Village, Lalolae District, East Kolaka Regency as many as 32 people, sampling using census techniques with data collection methods carried out by means of surveys, interviews, and documentation. Data were collected using a research questionnaire using a Likert scale. The selection of the research location was carried out purposively with the consideration that the research location is one of the villages where most of the people work as farmers and utilize Facebook social media to get information related to vegetable cultivation. This study used class interval analysis and correlation (Rank Spearman) with the help of SPSS version 22. The results showed that the use of Facebook social media (Context, Communication, Collaboration) and the competence of vegetable farmers in Lalosingi Village were in the high category seen from the knowledge, attitudes and skills possessed by farmers in vegetable cultivation. There is a significant relationship between the use of Facebook social media and the competence of vegetable farmers in Lalosingi Village.